ALTERNATIF STRATEGI PEMASARAN BAWANG PUTIH DI KECAMATAN TAWANGMANGU - mahananto; Ratih Dwi Kartikasari; endang suprapti (JURNAL ILMIAH AGRINECA, 2021)
This study aimed to determine what internal and external factors affect the marketing of garlic in the Ngudi Rejeki farmer group in Tawangmangu District. The method of determining the sample was purposive sampling with the snowball technique and the number of samples is 8 key respondents. Factors analyzed are management, production, marketing, government, competitors, consumers, socio-cultural, and information technology. The study was conducted from January to March 2021 in Tawangmangu District, especially the Ngudi Rejeki Farmer Group. The analytical methods used are IFE, EFE, and SWOT Matrix. The results showed that several alternative strategies that can be done are maintaining and improving the quality of the garlic produced, optimizing farmer group institutions to build a system with consumers without intermediaries, optimizing the role of extension workers and the government in garlic development and marketing, maintaining consumer confidence with farmer group management. good practices, and optimal use of technology such as cooperating with agricultural e-commerce.